Personality, Political Behavior, and Political Views about Mexico’s 2012 Presidential Election - Moreno, Alejandro; Wals, Sergio C. (Revista Debates, 2014)
People’s electoral behavior is understood as political predispositions and attitudes in specific institutional contexts. Recent scholarly work has included personality as a key explanatory factor in individual-level models of political participation. In this paper we build upon these recent efforts. We utilize the Big Five approach to assess the effects of different personality traits on people’s likelihood of political engagement during the 2012 presidential election in Mexico. We focus on the effects of personality on voting in the election and on individual views about the integrity of the electoral process. We use post election survey data collected for the Comparative National Elections Project in the 2012 Mexican presidential election. Our findings show that extraversion is a critical individual-level factor accounting for the propensity to turnout in this election as well as to encourage political discussion with family members, friends, neighbors, and co-workers.